The effects of a lesson study intervention on the teaching of electricity and magnetism - Gaigher, Estelle (University of Pretoria, 2018)
An in-depth case study was undertaken with the purpose of exploring teachers use of Lesson Study as they progressively strive to enhance their teaching of electricity and magnetism. A sample of four physical sciences teachers functioning separately as two lesson study pairs was conveniently selected from three different schools. Data were obtained through semi-structured interviews, individual teacher’s lesson observation and Lesson Study pair observation, field notes, document analysis of participants’ reflective writing and original lesson plan. The social constructivist learning approach of Vygotsky and the adult education approach of Malcolm Knowles was used as the theoretical framework of this study. Data obtained was analysed using qualitative content analysis. Results from this study indicates that individual interpretation of personal experiences and active collaboration with colleagues during Lesson Study meetings changed participants’ attitudes, beliefs and practices about teaching electricity and magnetism. Participants became more confident and competent teaching specific concepts in electricity and magnetism after the brainstorming sessions of the Lesson Study process. However, participants identified lack of support, unavailability of time and workload as contextual factors that might affect their continuous practice of the Lesson Study process. This study provides insight to how and why physical sciences teachers should collaboratively learn within the context of Lesson Study. It also contributes to the knowledge about how to promote effective and practical school based collaborative professional development programs among teachers. It is recommended that educational policy makers should develop strategic plans that allow teachers to engage in practical and effective collaborative professional development programs such as Lesson Study during the school day. Furthermore, the practice of collaborative teaching should start in teacher training programs to help reduce professional isolation among teachers.